Quantitative analysis of antibiotic usage in British sheep flocks - Davies, Peers; Remnant, John G.; Green, Martin J.; Gascoigne, Emily; Gibbon, Nick; Hyde, Robert; Porteous, Jack R.; Schubert, Kiera; Lovatt, Fiona; Corbishley, Alexander (BMJ Publishing Group, 2017)
The aim of this study was to examine the variation in antibiotic usage between 207 commercial sheep flocks using their veterinary practice prescribing records. Mean and median prescribed mass per population corrected unit (mg/PCU) was 11.38 and 5.95, respectively and closely correlated with animal defined daily dose (ADDD) 1.47 (mean), 0.74 (median) (R2=0.84, P<0.001). This is low in comparison with the suggested target (an average across all the UK livestock sectors) of 50 mg/PCU. In total, 80 per cent of all antibiotic usage occurred in the 39 per cent of flocks where per animal usage was greater than 9.0 mg/PCU. Parenteral antibiotics, principally oxytetracycline, represented 82 per cent of the total prescribed mass, 65.5 per cent of antibiotics (mg/PCU) were prescribed for the treatment of lameness. Oral antibiotics were prescribed to 49 per cent of flocks, 64 per cent of predicted lamb crop/farm. Lowland flocks were prescribed significantly more antibiotics than hill flocks. Variance partitioning apportioned 79 per cent of variation in total antibiotic usage (mg/PCU) to the farm level and 21 per cent to the veterinary practice indicating that veterinary practices have a substantial impact on overall antimicrobial usage. Reducing antibiotic usage in the sheep sector should be possible with better understanding of the drivers of high usage in individual flocks and of veterinary prescribing practices.